Endoscopic cystoventriculostomy of an arachnoid cyst using a neuroendovascular stent to maintain patency. (2nd January 2022) - Ghorbani, Mohammad; DeHoff, Grace; Griessenauer, Christoph J.; Mollahoseini, Reza; Shojaei, Hamidreza; Azar, Maziar
Abstract: Introduction: Cystoventriculostomy is a surgical treatment for arachnoid cysts. We present a case using a neuroendovascular stent to maintain ostomy patency. Case report: A 6½-year-old male with symptomatic arachnoid cyst underwent endoscopic fenestration and Wingspan stent insertion. Conclusion: Neuroendovascular stent placement may be an adjunct to maintain patency in cystoventriculostomy.